Principals’ Management Empowerment Practices and Its Relationship with Work Satisfaction Among School Mid-Level Administrators - Taising, Rutil; Karuppannan, Gunasegaran (Selangor Humaniora Review, 2020)
Principals' leadership that is based on management empowerment practices is one approach that has a significant impact on school success. The study attempts to investigate the relationship between principal’s management empowerment practices and the level of job satisfaction among school mid-level administrators. A quantitative approach was employed to examine the extent to which the five-dimensional management empowerment practices, namely decision making, professional development, status of responsibility, impact, and autonomy are related to the level of job satisfaction of mid-level administrators in Malaysian secondary schools. The data were obtained from 118 respondents using a set of questionnaires. The findings of the study show that gender factors and positions held are not significantly related with the level of job satisfaction among school administrators. Nonetheless, the five dimensions in the principals’ management empowerment practice were all found to have a significant, positive, and strong correlation with the administrators’ level of job satisfaction.